Tourists’ Acceptance Analysis Of Tourism Village Website Towards The Motivation To Visit - Cynthia Deborah Nababan; Dana Indra Sensuse; Ryan Randy Suryono; Kautsarina Kautsarina (Green Publisher Indonesia, 2024)
The development of tourism village websites aims to promote the potential of tourism villages in Indonesia. However, the increasing use of social media has reduced the intensity of websites being used. This research aims to determine whether the tourism village websites still influence tourists to visit the tourism village and whether it is relevant to the government's goals. Data was collected by distributing questionnaires and producing a valid sample of 242 respondents who actively use the Internet and have the potential to travel. The research model design was created by combining the DeLone & McLean IS success model with the Technology Acceptance Model (TAM). Data were analysed using the Structural Equation Modeling Partial Least Square (SEM PLS). The results show that the variables of information quality, service, and design positively affect trust, usability, ease of use, and enjoyment, positively affecting the intention to use the website. However, trust does not significantly influence the intention to use the website on the acceptance model. The frequent use of the tourism village website positively affects the tourist's motivation for the actual visit. Therefore, deeper analysis is needed to determine the variables that affect tourist confidence in developing acceptance models for further research. In addition, this research has practical implications for the government in making decisions regarding developing tourism village websites in terms of interface, user experience, information, and features.